Occupational therapy to improve outdoor mobility after stroke - Logan, Philippa A. (2005)
People who have suffered a stroke can become housebound and miserable because they cannot access suitable transport. They can have difficulty getting to the shops, doctors and hospital and this can have an effect on their quality of life. Occupational therapists routinely aim to help these people overcome their outdoor mobility problems by providing information and verbal instructions but these interventions do not appear to be effective. The aim of this research was to design and evaluate a new occupational therapy outdoor mobility intervention. The intervention was modeled on travel training that is provided for other conditions and the outdoor mobility experiences and needs of people with stroke.